PENINGKATAN DAYA SAING USAHA EKONOMI PRODUKTIF (UEP) MELALUI RENCANA PENGEMBANGAN APLIKASI ECOMMERS JUAL-BELI PERTAMA TALUY-JO DI KOTA KOTAMOBAGU - Olii, Rahmat; Adam, Anita Mafilinda; Manurung, Sri Juliani; Zakaria, Muhamad (Fakultas Teknik, Universitas Bangka Belitung, 2024)
This community service activity aims to analyze the improvement of the competitiveness of Productive Economic Enterprises (UEP) through the development plan of Taluy-Jo's first buy-and-sell E-commerce application in Kotamobagu City. UEP is social assistance from the Ministry of Social Affairs of the Republic of Indonesia provided to joint business groups to increase family income and social welfare. By integrating e-commerce technology, this community service activity aims to improve efficiency and market access for UEP with the planned use of the Taluy-Jo application. The research methods used include qualitative analysis with literature studies, surveys, and interviews with UEP owners and potential application users. This community service activity is expected to provide an in-depth understanding of the impact of e-commerce technology implementation on UEPs and provide strategic recommendations to improve their competitiveness. Thus, this research will make a positive contribution to local economic development, UEP growth, and e-commerce application development in Kotamobagu City area.